The impact of China's soft power policy and Mongolia (Journal of International Studies, 2023)
Abstract: As China's development and strength have garnered increasing global attention, concerns about this growth and development have also risen. Consequently, there is a growing need to better understand and promote China to the world, dispelling any apprehensions about its growth. To address this, China has been actively pursuing a soft power policy. The country places significant emphasis on its cultural aspects within its soft power policy, highlighting the promotion of its unique culture with a history spanning thousands of years, as well as the ideals and achievements of Chinese Marxist culture as key elements of its soft power strategy.This article briefly touches upon the primary component of China's cultural soft power policy, known as the "Going global" strategy. It discusses the use of Chinese language education, media, and cinema as instrumental tools for cultural diplomacy, and how this policy is being implemented in Mongolia, within the context of the industry. БНХАУ-ын Зөөлөн хүчний бодлогын онцлог ба Монгол УлсХураангуй: Хятад орон хөгжин хүчирхэгжиж буй нь дэлхий нийтийн анхаарлыг татаж эхэлснээр энэ өсөлт хөгжлөөс айх болгоомжлох хандлага ч их болсон. Иймд Хятад улсыг дэлхий дахинд илүү сайн ойлгуулж танин мэдүүлэх, Хятадын өсөлтөөс айх хэрэггүй гэдгийг сурталчлах шаардлага тулгарснаар зөөлөн хүчний бодлого эрчимтэй явуулж байна. Хятад улс зөөлөн хүчний бодлогодоо “соёл”-ыг онцлон олон мянган жилийн түүхтэй өвөрмөц соёл болон Хятадын онцлогтой марксист соёлын үзэл санаа, ололт амжилтыг сурталчлахыг Хятадын зөөлөн хүчний бодлогын онцлог гэж үзжээ. Энэ өгүүлэлд Хятадын соёлын зөөлөн хүчний бодлогын гол стратеги болох “Соёлын гадагш гарах” стратегийн тухай товч дурдаж, хятад хэлний боловсрол, хэвлэл мэдээлэл, кино урлаг зэрэг салбарыг соёлын дипломат ажиллагааны арга хэрэгсэл болгон ашиглаж байгаа байдал ба Монгол Улсад энэ бодлого хэрхэн хэрэгжиж байгааг дээрх гурван салбарын хүрээнд авч үзэв.  Түлхүүр үг: Хятад улс, соёлын зөөлөн хүч, гадагш гарах стратеги, хятад хэл, хэвлэл мэдээлэл, кино урлаг